BH3 Mimetics for the Treatment of Prostate Cancer - Wolf, Philipp (Frontiers in Pharmacology, 2017)
Despite improved diagnostic and therapeutic intervention, advanced prostate cancer (PC) remains incurable. The acquired resistance of PC cells to current treatment protocols has been traced to apoptosis resistance based on the upregulation of anti-apoptotic proteins of the Bcl-2 family. The use of BH3 mimetics, mimicking pro-apoptotic activator or sensitizer proteins of the intrinsic apoptotic pathway, is therefore a promising treatment strategy. The present review gives an overview of preclinical and clinical studies with pan- and specific BH3 mimetics as sensitizers for cell death and gives an outlook how they could be effectively used for the therapy of advanced PC in future.